Long-gap esophageal atresia: is native esophagus preservation always possible? - Treccarichi, G. M.; Di Benedetto, V.; Loria, G.; Scuderi, M. G. (Frontiers in Pediatrics, 2024)
Introduction: Esophageal atresia (EA) is a congenital defect that causes esophageal discontinuity, often with an associated tracheo-esophageal fistula (TEF) in 70-90% of cases. When the distance between esophageal ends precludes primary anastomosis, it results in long gap esophageal atresia (LGEA), complicating the surgical management. This study retrospectively reviewed LGEA cases from the past decade, treated with the goal of preserving the native esophagus, comparing surgical techniques and outcomes with current literature.The data of patients treated for LGEA between 2013 and 2024 were collected from medical charts, focusing on patients treated with the preservation of their native esophagus. Results: Ten patients were enrolled for this study. All of them had a gap between the esophageal ends equal to or greater than three vertebral bodies. Four patients (40%) underwent a delayed primary anastomosis (DPA) procedure, while the remaining six (60%) underwent a traction staged repair. All patients were treated with open surgery. The follow-up period extended from 3 months to 10 years.LGEA is a challenging but feasible goal, with delayed primary anastomosis and traction techniques playing key roles. We advocate for the preservation of the native esophagus as the preferred approach for ensuring a high quality of life for patients, as it helps to avoid severe long-term complications associated with esophageal substitution.